2011
DOI: 10.1038/nrmicro2613
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A viruses: new research developments

Abstract: Influenza A viruses are zoonotic pathogens that continuously circulate and change in several animal hosts, including birds, pigs, horses and humans. The emergence of novel virus strains that are capable of causing human epidemics or pandemics is a serious possibility. Here, we discuss the value of surveillance and characterization of naturally occurring influenza viruses, and review the impact that new developments in the laboratory have had on our understanding of the host tropism and virulence of viruses. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
468
0
9

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 536 publications
(498 citation statements)
references
References 147 publications
2
468
0
9
Order By: Relevance
“…Influenza provides a particularly interesting historical example (Table 6). Through 80 y of superb research on influenza viruses, we have learned much about the pathogenicity of these viruses in cells in vitro, in animal models in vivo, and in humans in natura, as well as the epidemiological course of seasonal and pandemic infections (124)(125)(126). However, we still know little about the determinism of life-threatening influenza, which occurs in only a minority of infected individuals in the course of epidemic or pandemic influenza (127).…”
Section: Influenza As Another Genetic Diseasementioning
confidence: 99%
“…Influenza provides a particularly interesting historical example (Table 6). Through 80 y of superb research on influenza viruses, we have learned much about the pathogenicity of these viruses in cells in vitro, in animal models in vivo, and in humans in natura, as well as the epidemiological course of seasonal and pandemic infections (124)(125)(126). However, we still know little about the determinism of life-threatening influenza, which occurs in only a minority of infected individuals in the course of epidemic or pandemic influenza (127).…”
Section: Influenza As Another Genetic Diseasementioning
confidence: 99%
“…Infl uenza A virus is an enveloped negative-stranded RNA virus with 8 gene segments (Medina and Garcia-Sastre, 2011). Gene reassortment occurs frequently to produce emerging viruses (Peiris et al, 2007).…”
Section: Structural Basis For Receptor-binding Changesmentioning
confidence: 99%
“…There are four recorded pandemics in the history, 1918 Spanish flu, 1957 Asian flu, 1968 Hong Kong flu and 2009 pH1N1 pandemic, with a less severe pandemic in 1977, Russian fl u (Medina and Garcia-Sastre, 2011). It has been shown that these viruses were linked to avian infl uenza viruses, with…”
Section: Introductionmentioning
confidence: 99%
“…In humans and animals, influenza is an acute respiratory disease that is caused by influenza virus A, influenza virus B, and influenza virus C. Influenza viruses belong to the Orthomyxoviridae family and have a negative sense RNA genome [24]. …”
Section: Introductionmentioning
confidence: 99%